2018
DOI: 10.1007/s10522-018-9761-9
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes: role in cellular ageing and age related disorders

Abstract: Peroxisomes are dynamic organelles essential for optimum functioning of a eukaryotic cell. Biogenesis of these organelles and the diverse functions performed by them have been extensively studied in the past decade. Their ability to perform functions depending on the cell type and growth conditions is unique and remarkable. Oxidation of fatty acids and reactive oxygen species metabolism are the two most important functions of these ubiquitous organelles. They are often referred to as both source and sink of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 200 publications
0
25
0
Order By: Relevance
“…Last but not least, they are involved in fundamental vital processes such as the detoxification of dangerous oxygen/nitrogen species (Fransen et al 2012 ), are signalling platforms (Mast et al 2015 ), with critical roles for innate immunity (Dixit et al 2010 ) as well as development and differentiation (Titorenko and Rachubinski 2004 ), and intimately communicate with other organelles (Schrader et al 2013 ; Shai et al 2016 ). Dysfunctions or even lack of peroxisomes not only underlie the well-known peroxisomal disorders, but also contribute to physio- as well as patho-physiological processes such as ageing and related diseases (Deori et al 2018 ) or cancer (see “ Peroxisomes and cancer: a mysterious connection ”).…”
Section: Mysterious Functions: An Update On Peroxisomal Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, they are involved in fundamental vital processes such as the detoxification of dangerous oxygen/nitrogen species (Fransen et al 2012 ), are signalling platforms (Mast et al 2015 ), with critical roles for innate immunity (Dixit et al 2010 ) as well as development and differentiation (Titorenko and Rachubinski 2004 ), and intimately communicate with other organelles (Schrader et al 2013 ; Shai et al 2016 ). Dysfunctions or even lack of peroxisomes not only underlie the well-known peroxisomal disorders, but also contribute to physio- as well as patho-physiological processes such as ageing and related diseases (Deori et al 2018 ) or cancer (see “ Peroxisomes and cancer: a mysterious connection ”).…”
Section: Mysterious Functions: An Update On Peroxisomal Metabolismmentioning
confidence: 99%
“…In view of their diverse metabolic functions, in particular their role both as source and sink of ROS in a cell, peroxisomes are a predestined hub in cellular ageing. Indeed, a plethora of studies employing cell lines of diverse origin, animals, and yeast cultures report on profound alterations in the biogenesis and proliferation of the organelle, in the rate of expression as well as location of peroxisomal enzymes engaged in ROS metabolism (catalase), and last but not least in the interaction with other cell organelles, particularly mitochondria (Deori et al 2018 and ref. therein).…”
Section: Mysterious Messengers: Peroxisomes In Signalling and Antivirmentioning
confidence: 99%
“…Metabolic reprogramming is one of the core traits of the cancer cells, due to the multiple alterations during the multi-step process of tumorigenesis (Soga, 2013;El Hassouni et al, 2019). In recent years, with the deepening understanding of the important functions of the peroxisomes, more and more attention were paid to the peroxisomes research (Tanner et al, 2013;El Hassouni et al, 2019) and they were demonstrated to be implicated in innate immunity (Ferreira et al, 2019), signal transduction (Schrul and Schliebs, 2018), aging (Deori et al, 2018), and cancer (Dahabieh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Given the evolutionary conservation of this and many other peroxisome biogenesis factors, it would be interesting to test the contribution of peroxisomes in genome maintenance during mammalian cell aging and cancer development. Indeed, several studies have reported the absence of peroxisomes in cancer cells [8991], suggesting a possible link between peroxisome biogenesis defects and tumorigenesis [92].…”
Section: Discussionmentioning
confidence: 99%